An 11-Year-Old Child with Autosomal Dominant Polycystic Kidney Disease Who Presented with Nephrolithiasis - Fatih Firinci; Alper Soylu; Belde Kasap Demir; Mehmet Turkmen; Salih Kavukcu (Case Reports in Medicine)
Patients with autosomal dominant polycystic kidney disease become symptomatic and are diagnosed usually at adulthood. The rate of nephrolithiasis in these patients is 5–10 times the rate in the general population, and both anatomic and metabolic abnormalities play role in the formation of renal stones. However, nephrolithiasis is rare in childhood age group. In this paper, an 11-year-old child with autosomal dominant polycystic kidney disease presenting with nephrolithiasis is discussed.